2020
DOI: 10.1177/1073191120927782
|View full text |Cite
|
Sign up to set email alerts
|

Initial Investigation of the Psychometric Properties of the Limited Prosocial Emotions Questionnaire (LPEQ)

Abstract: Callous–unemotional traits, which include lack of remorse or guilt, callousness/lack of empathy, unconcern about performance, and shallow/deficient affect, were included as a specifier of conduct disorder in the current (fifth) edition of the Diagnostic and Statistical Manual of Mental Disorders under the rubric Limited Prosocial Emotions (LPEs). The purpose of this study was to examine the psychometric properties of a new rating scale, the Limited Prosocial Emotions Questionnaire (LPEQ). Caregivers ( n = 1,05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…These results raise questions about the structure of the LPE specifier in the DSM-5. Although just one study, there is a clear need for continued research on, and perhaps refinement of the LPE specifier in the DSM-5 as rated by parents during childhood (Castagna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results raise questions about the structure of the LPE specifier in the DSM-5. Although just one study, there is a clear need for continued research on, and perhaps refinement of the LPE specifier in the DSM-5 as rated by parents during childhood (Castagna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the DSM-5-TR LPE diagnosis identifies a subgroup of children with more severe externalizing problems. Relative to boys and girls without an LPE diagnosis, children diagnosed with LPE had more severe externalizing problems (Castagna et al, 2021; Colins et al, 2021; Pardini et al, 2012), aggressive behavior (Bansal et al, 2023; Kahn et al, 2012; Pardini et al, 2012), cruel behavior to others and animals (Kahn et al, 2012), and risk of hurting others using a weapon (Déry et al, 2019). Children diagnosed with LPE also had greater global impairment and required more intensive treatment for their conduct problems (Castagna et al, 2021; Pardini et al, 2012).…”
Section: Utility Of the Dsm-5-tr Lpe Diagnosis In Young Childrenmentioning
confidence: 99%
“…To end, we would like to state that future research could be addressed to explore this mediational model, and the moderating effect of children’s age and sex, in young children with highly difficult temperaments, oppositional disorder or others childhood factors that could be of interest [ 72 , 73 ]…”
Section: Discussionmentioning
confidence: 99%